Crosslinked networks in electron beam irradiated polyethylenes evaluated by proton low-field NMR spectroscopy. (March 2023) - Posadas, Pilar; Valentín, Juan L.; Benavente, Rosario; Blázquez-Blázquez, Enrique; Urtiaga, Ane; Álvarez, Juan A.; Cerrada, María L.
Abstract: Effect of electron beam (EB) irradiation is analyzed in low and high density polyethylenes (LDPE and HDPE, respectively) at different doses. Parameters as important as degree of crystallinity, melting or crystallization temperatures are dependent on the initial PE molecular architecture, which also controls the gel content developed by action of EB irradiation and the EB dose applied. Thus, this gel amount, ascribed to formation of chain crosslinkings, is raised as irradiation dose increases, being larger in the HDPE than in the LDPE. In both, a plateau value is reached at the highest doses. The molecular changes that take place in both PEs during EB irradiation lead to a hindrance in their crystallization capacity, once macrochains are molten, and, accordingly, to a reduction in crystallinity and to formation of thinner crystallites. Variation with temperature of rigid and soft fractions together with their respective relaxation times is followed in the irradiated LDPE and HDPE specimens by pulse mixed magic-sandwich echo nuclear magnetic resonance (MSE-NMR) measurements. The network structure promoted in these PEs is evaluated by using the multiple-quantum nuclear magnetic resonance (MQ-NMR) approach, showing important differences caused by EB irradiation due to their intrinsic molecular characteristics. Highlights: Initial PE architecture controls gel content developed through EB irradiation. Crosslinking increases with EB doses, being more noticeable in HDPE than in LDPE. Values from three phase model agree better with crystallinity estimated by DSC. Relaxation times are much smaller in the rigid than in the soft phases for both PEs.